Pembangunan Sektor Pariwisata Berbasis Budaya Lokal di Sulawesi Selatan - Dahlan, Mubarak (Research Agency for Humanity and Urban, 2023)
The development of the tourism sector in recent years appears to have been increasingly intensive in various cities and districts throughout Indonesia. Several areas are being targeted for developing the tourism sector, such as: natural marine and beach tourism, city tourism, garden tourism, and culinary tourism. This article discusses strategies for developing the tourism sector, especially those related to local cultural aspects in South Sulawesi. This research is a type of literature review that uses data collection techniques through literature study. The research results show that the development of the tourism sector in South Sulawesi in recent years has not been fully based on and nuanced by local culture. However, on the other hand, local cultural heritage is actually something that is unique, so it can be used as basic capital to attract tourists to visit. Based on these conditions, it is necessary to promote tourism development that combines the concept with local cultural values.